2010
DOI: 10.1111/j.1365-2605.2008.00940.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Effects of exposure to a mobile phone on testicular function and structure in adult rabbit

Abstract: The accumulating effects of exposure to electromagnetic radiation emitted by a conventional mobile phone (standby position) on the testicular function and structure are not yet fully investigated. To study these effects longitudinally, a total of 24 adult male rabbits were randomly and equally divided into three groups. Rabbits in the first (phone) group were exposed, in specially designed cages, to radio frequency emitted from the mobile phone (800 MHz) in a standby position opposite to that of testes for 8 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 36 publications
2
22
0
1
Order By: Relevance
“…22 Third, the same group of MP animals represented the subjects of another two studies. Both indicated the negative influence of MPs on testicular function and structure 7 and semen fructose. 8 Interestingly, these retrieved findings were related to the oxidative stress occurring in the testes and accessory genital organs of the animals.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…22 Third, the same group of MP animals represented the subjects of another two studies. Both indicated the negative influence of MPs on testicular function and structure 7 and semen fructose. 8 Interestingly, these retrieved findings were related to the oxidative stress occurring in the testes and accessory genital organs of the animals.…”
Section: Discussionmentioning
confidence: 95%
“…The first group was the MP group whose members were placed individually in specially designed cages (50 Â 25 Â 35 cm) as they represented the same material used by some previous studies. 7,8 These cages could accept placing plastic partitions according to the animal dimensions (averaged 30 Â 16 Â 18 cm), to restrict movements. Therefore, the animals rested throughout the period of the daily phone exposure with their genitalia opposing the antennas of the MPs that were fixed to the cage bottoms.…”
Section: Copulatory Behavior Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiofrequency radiations affect Leydig cells [10], which are found adjacent to the seminiferous tubules. Moreover, a decrease in the diameter of seminiferous tubule [11,12], weight of testicular organs (i.e., caput, cauda, corpus) [13], and destruction of Leydig cells due to these radiations are possible indications of male infertility. More recently, several authors [14] have reported that electromagnetic wave affects sperm motility and it is known that a correlation exists between sperm motility and sperm chromatin damage [15].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the sperm motility is at the same level as control up to week 10 which was followed by a significant reduction in the group that was exposed to radiation compared to the control group [19].…”
Section: /9mentioning
confidence: 80%